Childfree Marriage in the Perspective of Maqashid Asy-Syari’ah - Dwi Arini Zubaidah (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2023)
Regarding the birth of children as one of the goals of marriage, recently there have been problems with issues and childfree practices among the general public. This research uses a type of normative legal research that originates from primary data related to the concept of childlessness, the theory of the purpose of marriage, and the maqashid asy-syari'ah system theory of Jasir 'Audah. This study uses a conceptual approach. collection of research data based on description and analysis Jasir Audah's system theory has six features: 1) the cognition character of the Islamic legal system; 2) the overall Islamic legal system; 3) the openness of the Islamic legal system; 4) the interrelated hierarchies of the Islamic legal system; 5) the multidimensionality of the Islamic legal system; and 6) the meaningfulness of the Islamic legal system. Based on Jasir 'Audah's maqashid asy-syari'ah system theory, it can be concluded that first, childfree decisions are recommended not to be made if the underlying factors do not endanger the existence of benefit values, and second, childfree decisions are allowed if there is an urgency for the existence of benefit.